2019
DOI: 10.1111/den.13549
|View full text |Cite
|
Sign up to set email alerts
|

Biliary stenting for hilar malignant biliary obstruction

Abstract: Although endoscopic intervention is the mainstay for palliation of malignant biliary obstruction, a percutaneous approach has been preferred, particularly in patients with advanced highgrade hilar malignant biliary obstruction, because of the technical difficulty and risk of complications. However, recently, primary endoscopic palliation using plastic or metal stents has had higher technical and clinical success with fewer adverse events than the percutaneous approach. Endoscopic interventions are being done m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 82 publications
0
70
1
Order By: Relevance
“…The RBO rate after placement of bilateral SEMS in MHO has been reported to range from 3% to 45%. 3 Therefore, following successful endoscopic deployment of bilateral SEMS, endoscopic or percutaneous reintervention for the previously inserted SEMS should be considered when RBO develops. However, various reinterventions, as well as the primary deployment of bilateral SEMS, are deemed to be technically difficult in MHO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RBO rate after placement of bilateral SEMS in MHO has been reported to range from 3% to 45%. 3 Therefore, following successful endoscopic deployment of bilateral SEMS, endoscopic or percutaneous reintervention for the previously inserted SEMS should be considered when RBO develops. However, various reinterventions, as well as the primary deployment of bilateral SEMS, are deemed to be technically difficult in MHO.…”
Section: Discussionmentioning
confidence: 99%
“…However, nowadays, the technical feasibility and clinical success rate of bilateral SEMS have been improved according to numerous recent studies, and bilateral drainage might be more effective physiologically for stent patency. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] A recent comparative study also showed that bilateral drainage using SEMS was more beneficial in stent patency than was unilateral drainage in advanced (MHO) without a difference in technical difficulty or adverse event rates. 2 For adequate liver drainage, multiple drainages are now considered as a primarily recommended method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple deployment of metal stents (MSs) in high‐grade malignant hilar biliary obstruction (MHBO) is technically challenging . Although combined side‐by‐side (SBS) and stent‐in‐stent deployment might reduce its difficulty, the insertion of the third MS remains a concern .…”
Section: Brief Explanationmentioning
confidence: 99%
“…T RIPLE DEPLOYMENT OF metal stents (MSs) in highgrade malignant hilar biliary obstruction (MHBO) is technically challenging. [1][2][3][4] Although combined side-by-side (SBS) and stent-in-stent deployment might reduce its difficulty, the insertion of the third MS remains a concern. 5 A new MS that has a 5.4-Fr ultra-thin delivery system (Zeo Stent V; Zeon Medical, Tokyo, Japan) was recently developed, and it facilitates simultaneous triple SBS deployment ( Fig.…”
mentioning
confidence: 99%